Xorazm xalq dostonlari vositasida bo‗lajak musiqa o‗qituvchilarining ma‘naviyatini rivojlantirish pedagogik muammo sifatida - Yakubov, Z.M (SCIENCE and SOCIETY, 2023)
This article discusses the spiritual development of future music teachers through Khorezm folk epics, the harmonious harmony of our national heritage with national traditions and customs, the preservation and enrichment of na- tional cultural samples, education as national recognition as the most important factor in development, the introduction of a new educational system aimed at respect for the history and culture of other peoples, factors are discussed to ensure the effectiveness of the educational process.
Keywords: national culture; laments and songs; folklore; music; educational technology; epic; classics